Reference intervals for hematological parameters of animals bred and kept at the vivarium of the Faculty of Medicine of the State University of São Paulo - Marilda Osti Spinelli; Milena Coutinho Motta; Robson José Cruz; Cynthia Marques Santos Corrêa Godoy (Universidade Estadual de Maringá, 2014)
Knowledge of specific hematological parameters of laboratory animals used in experiments is highly relevant to evaluate functional alterations of their vital organs. Hematological reference rates for rats, mice, rabbits and hamsters, bred in conventional healthy conditions and derived from the Vivarium of the FMUSP's Vivarium Center are established. One hundred and twenty mice of the strains BALB/c, C57BL / 6 and Swiss, 80 Wistar rats, 80 Golden hamsters and 80 New Zealand rabbits, males and females, apparently normal and healthy, over 10-weeks-old, were employed in current experiment. The analysis was determined by flow cytometry process (CELM CC510) involving the separation of erythrocytes and leukocytes, and cell identification by the suspension method and quantification. Hematological derivatives such as hematometric indexes (application of equations) and morphological quantification of leukocytes and erythrocytes were determined by scanning/differential (Panótico-commercial), whereas hemoglobin dosage was determined by spectrophotometry (CELM E210D). Results are given as means and standard deviants of hematological profiles in the blood of the animals grouped by species, strain and sex. Data are an important asset for researchers in their analysis of experimental results. CEAU Certificate n.° 251/11 HCFMUSP.